Hepatoprotective Role of Gallic Acid on Sodium Fluoride-Induced Liver Injury in Rats - Bouasla, A; Bouasla, I; Boumendjel, A; El Feki, A; Messarah, M. (My University, 2014)
This study was undertaken to evaluate the protective effect of Gallic acid (GA) on oxidative damages in liver of rats intoxicated by sodium fluoride. Rats were randomly divided into three groups of six animals each: group (C): served as a control; group (NaF): treated for three weeks with sodium fluoride (100 ppm in drinking water) and group (NaF+GA) : treated daily and for three weeks also by both of NaF and GA (20mg/Kg orally). It was found that NaF induced liver damages as evidenced by the elevation of plasma amino transferases (ALT, AST), alkaline phosphatase (ALP), lactate dehydrogenase (LDH) activities associated with a decrease in total protein, albumin and bilirubin levels. Hepatotoxicity was objectified by the significant increase of malondialdehyde (MDA) level and a decrease of antioxidant enzyme activities such as catalase (CAT), superoxide dismutase (SOD), glutathione peroxidase (GPx) and reduced glutathione (GSH) in liver of NaF treated rats. However, the co-administration of gallic acid caused an amelioration of the previous parameters. This study clearly showed that gallic acid has protective role against the oxidative damage in sodium fluoride intoxicated rats. Keywords: Gallic acid, Hepatotoxicity, Oxidative stress, Rat, Sodium fluoride